Experimental Investigation on the Effect of Web Opening Dimension on the Behavior of R/C Hybrid Deep T-Beam Subjected to Pure Torsion - Lisantono, Ade; Besari, Mohamad Sahari; Suhud, Ridwan; Soemardi, Biemo W (Institut Teknologi Bandung, 2004)
Abstract. An experimental study was conducted to investigate the effect of web opening dimension on the behavior of reinforced concrete hybrid deep T-beam subjected to pure torsion. Four reinforced concrete hybrid deep T-beams were tested under pure torsion, where the three beams with different dimension of circular web opening and the other beam without opening as a reference beam. The testing program and experimental results are presented. The results show that dimension of circular web opening with diameter more than 100 mm significantly reduces the cracking and ultimate torque. It is also shown that the angle of crack inclination with respect to the longitudinal axis of the beam increases with the increase of web opening dimension. Abstrak. Suatu studi eksperimental telah dilakukan untuk meneliti pengaruh dimensi bukaan pada perilaku balok tinggi-T hybrid beton bertulang yang dikenai torsi murni. Empat balok diuji dibawah beban torsi murni, dimana tiga balok mempunyai dimensi bukaan yang berbeda dan satu balok tanpa bukaan sebagai tolok ukur. Program pengujian dan hasil-hasilnya disajikan dalam makalah ini. Hasil pengujian memperlihatkan bahwa dimensi bukaan dengan diameter lebih dari 100 mm secara signifikan mengurangi kekuatan torsi pada saat retak dan saat maksimum. Hasil eksperimental juga menunjukkan bahwa sudut kemiringan retak terhadap sumbu memanjang balok meningkat dengan meningkatnya dimensi bukaan.